Factors Associated With The Level Of Compliance In The Use Of Masks In The Community During The Covid-19 Pandemic In The Village Reuhat Tuha District Aceh Besar In 2021 - Nur Rahmi, Asnawi Abdullah, Fahrisal Akbar (Journal of Health and Medical Science, 2022)
Masks are one of the important personal protective equipment during the COVID-19 pandemic to avoid the spread of the virus. COVID-19 cases are increasing every day. However, community compliance with the use of masks is still not optimal, one of which is in Aceh Province, community compliance with masks tends to decrease, the lowest district is Aceh Besar District with a compliance rate of 53.3%. The purpose of this study was to determine the relationship between knowledge, attitudes, sources of information, monitoring systems, and barriers to the use of masks with adherence to the use of masks in the community during the COVID-19 pandemic, Reuhat Tuha Village, Aceh Besar District in 2021. Methods: This study was conducted using a descriptive analytical method. with a cross sectional approach. The sample in this study was the people of Reuhat Tuha Village as many as 80 respondents, with the sampling technique of Simple Random Sampling. This research was conducted on 19 to 26 August 2021. Data analysis used Chi-Square statistical test with SPSS version 22.0 program. Results: The results showed that there was a significant relationship between knowledge (p-value 0.001), attitude (p-value 0.001), supervision system (p-value 0.005), and barriers to using masks (p-value 0.001) with adherence to the use of masks. in the community during the COVID-19 pandemic. While the source of information (p-value 0.219) has no relationship with the compliance of the use of masks in the community during the COVID-19 pandemic. Suggestion: It is hoped that the community will prioritize the benefits of using masks rather than discomfort for safety and health during the COVID-19 pandemic, and increase their sense of caring for fellow community members to remind each other if there are still people who do not comply with wearing masks. Because the use of masks has now become a new habit that must always be applied.